A descriptive epidemiological study of the prevalence of self-reported sensory difficulties by age group, sex, education, disability, and migration status in Sweden in 2020 - Andreea-Corina Badache; Elina Mäki-Torkko; Stephen Widen; Stefan Fors (BMC Public Health)
Abstract Background The objective of this study is to estimate the prevalence of self-reported hearing difficulties, vision difficulties and combined vision and hearing difficulties in a Swedish adult population that varies according to migration status, sex, age, disability measured by ADL and IADL and educational attainment level. Methods The study utilised data from the Survey of Health, Ageing and Retirement in Europe, which consisted of 2257 individuals aged 60 and above that were interviewed in Sweden in the 2019/2020, SHARE wave 8. To determine the prevalence of sensory difficulties (hearing, vision and dual-sensory difficulties) among various subgroups of the population, a multinomial logistic regression was used. The results of these analyses are presented in terms of predicted probabilities. Results The study findings indicate that foreign-born older adults experience a lower prevalence of visual difficulties (6.2% [3.3–11.5] in comparison to their Swedish-born counterparts. Moreover, older adults with higher levels of education tend to report a lower prevalence of sensory difficulties overall. Furthermore, sex differences are apparent, with males reporting a higher prevalence of hearing difficulties (18.9% [15.5–22.8] vs. 12.8% [10.7–15.3]) and females reporting a higher prevalence of vision difficulties (12.7% [10.7–15.1] vs. 8.5%[6.8–10.5]). Conclusion The findings highlight disparities in the prevalence and type of perceived sensory difficulties experienced by older adults, by factors such as age, sex, education and migration status. It is important to consider these demographic factors in healthcare planning and interventions aimed at mitigating sensory difficulties in the older population.